"We're on the ground, we know what needs to be done": Exploring the role of Aboriginal Health Workers in primary health care - Ragavi Jeyakumar; Ragavi Jeyakumar; Bindu Patel; Julieann Coombes; Ty Madden; Rohina Joshi; Rohina Joshi; Rohina Joshi (Frontiers Media S.A., 2023)
BackgroundAboriginal Health Workers (AHWs) are core providers of primary health care (PHC) for First Nations peoples in Australia. However, the national AHW workforce is aging and in short supply. There is a poor understanding of the factors contributing to this attrition from the perspectives of AHWs themselves. This study aimed to systematically explore the current functioning and sustainability of AHWs in NSW PHC by amplifying AHW voices.Materials and methodsThis study was co-designed with three Aboriginal health services in NSW. It included a literature review exploring the role of AHWs in NSW, and yarns with AHWs and their supervisors at participating services. Yarning is an Indigenous approach to knowledge generation centered upon storytelling. The yarns were guided by the USAID-developed Community Health Worker Assessment and Improvement Matrix. Yarn transcripts were analyzed using cyclical thematic analysis to identify key facilitators and challenges for AHW practice.ResultsThe yarns highlighted five categories of change that are required to ensure AHW sustainability: community connection, recognition, value, support, and an inclusive health system. The yarns revealed that there are both service- and system-level factors influencing each of these categories of change.ConclusionsThe lived experiences of AHWs in NSW emphasize five key categories of change that are required to ensure workforce sustainability. It is evident that a system-wide paradigm shift to better include holistic approaches to health is necessary to truly ensure sustainability. Co-designing similar studies with ACCHOs across NSW can help inform this change.